Effect of plant spacing on flower and seed production in different strains of gomphrena (Gomphrena globosa) (Current Horticulture, 2024)
The experiment was conducted to find out the effect of plant spacing on flower and seed production in gomphrena (Gomphrena globosa L.)" at the experimental farm of Department of Floriculture and Landscape Architecture, Dr. Yashwant Singh Parmar University of Horticulture and Forestry, Nauni, Solan, during 2013. The experiment was laid out in randomized block design (factorial) with four levels of spacings, viz. (20 cm × 15 cm, 20 cm × 20 cm, 20 cm × 25 cm, 20 cm × 30 cm) with three strains i.e. GGW (Gomphrena globosa 'White'), GGM (Gomphrena globosa 'Magenta') and GGP (Gomphrena globosa 'Pink'). Among different plant spacings, closest spacing of 20 cm × 15 cm gave best results for plant height (59.10 cm), earlier arrival of visible flower bud stage (52.00 days), flower yield/m2 (1,253.13 g) and seed yield/m2 (83.34 g). However, plant spread (44.88 cm), number of flowers/plant (72.11), flower diameter (2.31 cm), duration of flowering (96.55 days), weight of flowers/plant (65.79 g) and seed yield/plant (83.34 g) were maximum with 20 cm × 30 cm spacing. Among strains, GGM gave best results for plant height (54.65 cm), weight of flowers/plant (57.00 g), seed yield/plant (3.57 g), 1000 seed weight (3.49 cm), flower/yield m2 (1,253.13 g) and seed/yield m2 (75.14 g). Based upon the overall performance of different strains, a closest spacing of 20 cm × 15 cm was recommended under midhill zones of Himachal Pradesh.
Keywords: Plant spacing; Flower yield; Seed yield; Strains; Flower diameter